A COLLABORATIVE SHARING OF STORIES ON A JOURNEY TOWARD RECONCILIATION: “BELONGING TO THIS PLACE AND TIME” - Keliipio, Kauʻi; Perry, Kimberly; Elderton, Colleen (McGill Journal of Education / Revue des sciences de l'éducation de McGill, 2018)
This paper emerges from the particular field experiences of three “settler” colleagues working in a teacher education program, each of whom found that their personal and professional relationships with First Nations, Metís, and Inuit people had a positive and constructive bearing on how they responded to provincial mandates and the Truth and Reconciliation Commission’s Calls to Action.